The association positive and negative empathy have with depressive symptoms, resilience, and posttraumatic growth - Taylor Elam; Amber Efthemiou; Kanako Taku (Scientific Reports)
Abstract Empathy, the ability to understand and respond to others’ emotional experiences, is often regarded as a universally positive trait. However, its role in psychological adjustment following adversity is more complex. The current study examined the relationships between empathy – measured globally and through its positive (compassionate concern) and negative (callousness) dimensions – and three outcomes of stress or trauma: depressive symptoms, resilience, and posttraumatic growth (PTG). College students (N = 403) completed online surveys assessing these variables, with controls for age, sex, and personality traits. Hierarchical regression analyses showed that global and positive empathy were positively associated with PTG, indicating empathy’s role in fostering personal and relational growth. However, positive empathy also predicted depressive symptoms, reflecting its potential to heighten vulnerability to emotional distress. Negative empathy was inversely related to PTG but unrelated to depressive symptoms or resilience. Resilience demonstrated weaker links with empathy, instead aligning more closely with personality traits like extraversion and conscientiousness. These findings highlight empathy’s dual impact, where it can contribute to personal growth while also increasing susceptibility to distress. Future research should explore empathy’s cognitive and affective components and develop strategies to minimize its negative effects while enhancing adaptive outcomes like PTG.